Optimizing wireless channel using adaptive modulation to improve QoS in VANET - Christopher, C.; Noor, R.M.; Mostajeran, E. (2013)
Vehicular Ad Hoc Network (VANET) is a multi-hop wireless network which involves vehicles acting as nodes to communicate with each other without infrastructural support. With the increase in Quality of Service (QoS) needs in evolving applications and the widespread use of wireless and mobile devices, it is desirable to support QoS in VANETs. The resource limitations and variability further add to the need for QoS support in such networks. However, the characteristics of these networks make QoS support a complex process due to rapid topology changes caused by high mobility of communicating nodes. Modulation scheme implemented in wireless network affect the data rate hence the throughput of the communicating nodes, this in turn affect QoS. The paper focuses on adaptive modulation to improve the data throughput and efficiency of channel spectrum in VANET. Through theoretical and simulation results, it was shown that adaptive modulation performs well and improves throughput than other modulations schemes when used singularly in dynamic changing network topology like VANET.